Old Info for a New Fisheries Policy: Discard Ratios and Lengths at Discarding in EU Mediterranean Bottom Trawl Fisheries - Tsagarakis, Konstantinos; Carbonell, Ana; Brčić, Jure; Bellido, Jose M.; Carbonara, Pierluigi; Casciaro, Loredana; Edridge, Alexius; García, Teresa; González, Maria; Krstulović Šifner, Svjetlana; Machias, Athanassios; Notti, Emilio; et al. (Frontiers in Marine Science, 2017)
Discarding is considered globally among the most important issues for fisheries management. The recent reform of the Common Fisheries Policy establishes a landing obligation for the species which are subject to catch limits and, in the Mediterranean, for species which are subject to Minimum Conservation Reference Size (MCRS) as defined in Annex III to Regulation (EC) No 1967/2006. Additionally, several other initiatives aim to reduce unwanted catches of target and bycatch species, including species of conservation concern. This raises the need to study discarding patterns of (mainly) these species. In this work we collated a considerable amount of historical published information on discard ratios and lengths at discarding for species caught in EU Mediterranean bottom trawl fisheries. The main aim was to summarize the available historical records and make them more accessible for scientific and managerial needs, as well as to try identifying patterns in discarding. We show discard ratios and lengths at which 50% of the individuals were discarded (L50) for 15 species (nine bony fishes, three crustacean decapods and three elasmobranchs). Discard ratios were usually low for target species such as hake, red mullets and highly commercial shrimps and exemptions from the landing obligation under the de minimis rules could be sought in several cases. Discard ratios were usually higher for commercial bycatch species. Discarding is affected by a combination of factors and for a given species, especially for non-target ones, discards are likely to fluctuate within a fishery, across seasons, years and regions. For most species considered, L50s were lower than the MCRS (when in place) and length at first maturity. L50s of target species, such as hake, were very small due to the existence of market demands for small sized individuals. However, for species of low demand, like horse mackerels, a higher retention size was observed, often exceeding MCRS. Lengths at discarding are affected by legal provisions, market demands but also by biological, population and ecological traits. Understanding the factors that affect discarding constitutes the starting point for designing mitigation measures and management plans to reduce discards and improve the sustainability of the stocks.